How to take advantage of a new crop?: the experience of Melanesian smallholders - Feintrenie, L.; Ollivier, J; Enjalric, F (2010)
Coconut-based agroforestry systems have a central role in livelihoods on Malo Island in the South Pacific. These mixed plantations provide households with both food and a cash income, thanks to the association in space and time of root crops, vegetables, and cash crops (coconut, cocoa and vanilla). Vanilla has been developed on the island since the year 2000. Farmers have tried to adapt their production systems to include it, with some choosing to do so by associating vanilla with their main cash crop, coconut. A survey of these innovative practices and their economic results conducted in 2005 resulted in an economic modelling of this new agroforestry system with the software Olympe. This study illustrates the use of economic modelling with Olympe to simulate and test new agricultural practices in complex agroforestry systems. The software proved to suit agroforestry systems very well and provided useful information, particularly on economic aspects.